The importance of staff motivation in the company - Babik, Yulia; Bozhok, Natalia (My University, 2014)
Some employers think that paying their staff a good salary is enough to get the highest level of performance and some employers do not even do that. Paying a good salary is just not enough. Most employees still need to be motivated to increase their awareness of the status of the company, let them know what are expected of them and have them develop genuine care as to the growth and progress of the company they are working for. At the present time due to deepening of the globalization process Ukrainian enterprises are faced with the problem of increased competition and access to foreign markets. In our opinion, many of the problems and failures of integration into the world economy in Ukraine have been associated with problems in the area of human resource management, and particularly in performance motivation and staff retention.
Keywords: staff; resources chelovecheskye; motivation; мотивація; людські ресурси; персонал; человеческие ресурсы; мотивация; кафедра ділової іноземної мови та міжнародної комунікації